(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate the chemical composition, growth of microorganisms, and the aerobic stability of high-moisture corn grain silage inoculated with Lactobacillus plantarum + Propionibacterium acidipropionici. The experimental design was completely randomized in a 2 x 5 factorial arrangement with four replications (50 experimental units) and the treatments were: use or not of microbial inoculant (2 x 105 colony forming unit (CFU) g-1 Lactobacillus plantarum + Propionibacterium acidipropionici) and the storage length for 0, 1, 3, 7, and 14 d. Aerobic stability of silage was evaluated at 28 and 56 d of storage length. The lactic acid bacteria population was influenced by storage length and the greatest values were estimated at 8 d of storage length. Regardless of inoculant application, no enterobacteria were present from 3 d post-ensiling. With respect to mold growth, an interaction between inoculant and storage length was observed wherein molds were most abundant after 3 d of storage in silage that received inoculant. However, at 14 d of storage the use of bacterial inoculant reduced the occurrence of molds. pH values obtained after 3 d of ensiling were less than 4.0 for all the treatments. The high-moisture corn grain silage possessed good fermentative quality. Further, adequate pH values were achieved from the third day of ensilage and were not influenced by the presence of bacterial inoculant.